2019
DOI: 10.1002/hyp.13404
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation from seasonally frozen bare and vegetated ground at various groundwater table depths in the Ordos Basin, Northwest China

Abstract: In cold climates, the process of freezing–thawing significantly affects the ground surface heat balance and water balance. To better understand the mechanism of evaporation from seasonally frozen soils, we performed field experiments at different water table depths on vegetated and bare ground in a semiarid region in China. Soil moisture and temperature, air temperature, precipitation, and water table depths were measured over a 5‐month period (November 1, 2016, to March 14, 2017). The evaporation, which was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…It might be explained by the effects of soil freezing-thawing processes and snow sublimation on the winter ET. A previous study demonstrated that there exist several soil freezing-thawing cycles from late November to early March in arid regions of China, which could significantly affect land surface heat and water balance [47]. That is, ecosystem ET should be very small during the freezing periods due to the relatively less liquid soil moisture, and higher during the thawing periods [47].…”
Section: Dominant Factors Driving Interannual Variability Of Et In Thmentioning
confidence: 99%
See 1 more Smart Citation
“…It might be explained by the effects of soil freezing-thawing processes and snow sublimation on the winter ET. A previous study demonstrated that there exist several soil freezing-thawing cycles from late November to early March in arid regions of China, which could significantly affect land surface heat and water balance [47]. That is, ecosystem ET should be very small during the freezing periods due to the relatively less liquid soil moisture, and higher during the thawing periods [47].…”
Section: Dominant Factors Driving Interannual Variability Of Et In Thmentioning
confidence: 99%
“…A previous study demonstrated that there exist several soil freezing-thawing cycles from late November to early March in arid regions of China, which could significantly affect land surface heat and water balance [47]. That is, ecosystem ET should be very small during the freezing periods due to the relatively less liquid soil moisture, and higher during the thawing periods [47]. The ET over snow surface (i.e., snow sublimation) has been proved be positively correlated with air temperature [48].…”
Section: Dominant Factors Driving Interannual Variability Of Et In Thmentioning
confidence: 99%
“…As an associated process of soil water movement, salt accumulation or soil salinization is closely related to soil evaporation in arid and semiarid regions, even during freezethaw periods (Rose, Konukcu, & Gowing, 2005;Shimojimaa, Yoshioka, & Tamagawa, 1996;Zhang et al, 2019). Zhang and Wang (2001) investigated soil salinization during freeze-thaw periods in northeast China and found that salt moved upward and accumulated in the upper soil layer with water movement due to the frozen action in the freezing stage; salt was then deposited in the topsoil and/or crystallized at the ground surface with the continuous evaporation during the thawing stage of the next spring.…”
Section: Core Ideasmentioning
confidence: 99%
“…Moreover, the cumulative evaporation increased with increasing initial salt content and declined with lowering groundwater table depths. From the data of soil water and temperature measured by soil hydrothermal sensors, Zhang et al (2019) used a mass balance method to study soil evaporation from bare and vegetated ground at various groundwater table depths in lysimeters. Their results showed that soil evaporation was high during the thawing process and was low when the soil was freezing and that higher groundwater table depths resulted in greater cumulative evaporation levels.…”
mentioning
confidence: 99%
“…Seasonally frozen soil evaporation in cold regions is of significant importance to the global climate (Zhang et al, 2019) and a major process in the hydrological cycle. Seasonally frozen soil represents 50.5% of the total exposed land area in the Northern Hemisphere (Zhang, Barry, Knowles, Ling, & Armstrong, 2003).…”
Section: Introductionmentioning
confidence: 99%